Teak Extracts as a Delignification Catalyst of Soda Pulping - Deded S Nawawi; Suyono Suyono; Anjar A Widyorini (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
Teak wood (Tectona grandis) extracts which contain mainly 2-methylanthraquinone (natural MAQ) was utilized as an aditif of modified soda pulping. Dissolution of lignin and polysaccharides during initial delignification stage of cooking at 120 oC for 60 min, were analized. The additions of extracts were 0.05, 0.10, 0.15, and 0.20% of MAQ equivalent. Teak extracts play as a catalyst of delignification and polysaccharides stabilization, efectively. By addition of teak extract, the delignfication selectivity during initial stage of soda pulping increased significantly, even; it was much more effective than that of commercial anthraquinone. Accordingly, teak extracts which consist of 2-methylanthraquinone seems to be promising natural aditif for the alkaline pulping.Key words: delignification, soda pulping, teak extract, tectoquinone